Expression of tertiary lymphoid structure in deferred cytoreductive nephrectomy of metastatic renal cell carcinoma treated with nivolumab plus ipilimumab. Issue 6 (16th August 2021) - Sazuka, Tomokazu; Fujimoto, Ayumi; Sato, Hiroaki; Arai, Takayuki; Imamura, Yusuke; Sakamoto, Shinichi; Ikeda, Jun‐ichiro; Ichikawa, Tomohiko
Abstract : Introduction: Tertiary lymphoid structure expression and immune checkpoint inhibitors have been attracting attention, and their relationship with renal cell carcinoma is controversial. Case presentation: Two patients with nivolumab plus ipilimumab treatment response for metastatic renal cell carcinoma underwent cytoreductive nephrectomy and regional lymph node dissection. In both cases, the renal tumor site expressed tertiary lymphoid structures. Despite the absence of treatment after a deferred cytoreductive nephrectomy and the short postoperative observation period, the patients still survived. Conclusion: Tertiary lymphoid structures were expressed in deferred cytoreductive nephrectomy specimen in cases treated with nivolumab plus ipilimumab.